ANALYSIS OF FACTORS INFLUENCING GEN Z'S INTEREST IN INVESTING (CASE STUDY OF FEB STUDENTS OF MUHAMMADIYAH UNIVERSITY PURWOKERTO) - Pratamasari, Mega Aprillia; Rahmawati, Ika Yustina; Purwidianti, Wida; Kharismasyah, Alfato Yusnar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to examine the influence of investment knowledge, investment motivation, technological developments and financial literacy on investment interest. This research uses a quantitative approach method. The data source used in this research is primary data, using data collection techniques by distributing questionnaires via the Google From link. The population in this study were active FEB students at Muhammadiyah University Purwokerto who had opened stock accounts at the Sharia Investment Gallery of the Indonesian Stock Exchange, Faculty of Economics and Business, Muhammadiyah University Purwokerto (GISBEI FEB UMP), totaling 3,104 students. The data analysis method in this research uses SEM (Structural Equation Model) using the PLS (Partial Least Square) analysis program version 3.0. In this study, all instruments were valid and reliable. The research results show that investment knowledge has a positive and insignificant effect on investment interest. Investment motivation has a positive and significant effect on investment interest. Technological developments have a positive and insignificant effect on investment interest. And financial literacy has a positive and significant effect on investment interest.